Composição bioquímica e decomposição da parte aérea e raízes de culturas comerciais e plantas de cobertura de solo - Redin, Marciel (2010)
Crop residues (CR) composed by shoots and roots of plants are the main source of C for the agricultural soils. During the decomposition of these CR in the soil, part of C is evolved as CO2 and nutrients are mineralized, with emphasis on the N. Among the factors that affect decomposition of CR, the biochemical composition has great importance. The objectives of this study were: a) evaluate the dry matter production (DM) and biochemical composition of CR of shoot and roots from commercial and summer cover crops; and b) evaluate the influence of biochemical composition of the transformations of C and N, when CR are kept on the surface (shoot), or incorporated to soil (roots). It was realized two studies, in the first one, it was quantified the DM and biochemical composition of CR from shoot (leaves and stalks) and roots. In the second study, it was evaluated under laboratory conditions for 120 days, the mineralization of C and N and the results were correlated with the biochemical composition of the CR studied. The DM yield of roots varied from 0.54 to 2.86 Mg ha-1 in commercial crops and from 0.56 to 1.66 Mg ha-1 in cover crops. Rice and millet were the species that had the highest DM production of shoots and roots between the commercial and cover crops, respectively. Most of the DM of roots was found in the topsoil (0-10cm) and near the sowing row. The relation root/shoot average of cover crops was less than commercial crops (0.10 vs. 0.17). The CR show wide variation in their biochemical composition. The N content in the DM of CR ranged from 2.8 g kg- 1 (sunflower stalks) to 46.3 g kg- 1 (velvet leaves). The soluble fraction of Van Soest ranged from 108 g kg-1 (soybean stalks) to 774 g kg-1 DM (bean leaves). While the values of cellulose in DM ranged from 138 g kg-1 (bean leaves) to 612 g kg-1 (sunflower stalks), those of lignin ranged only from 38 g kg-1 in the leaves of Crotalaria juncea to 197 g kg- 1 in roots of soybean. The highest levels of polyphenols were found in the CR from shoot (14.1 g kg-1 DM) and roots (22.2 g kg-1 DM) of velvet beans. The CR with N content less than 15 g kg-1 (C/N > 29) cause net immobilization of N in the soil. All the roots of valued commercial crops caused immobilization of N in the soil, and the predominance of net mineralization of N was observed only with the roots of cover crops legume. In general, the mineralization of C from CR decreased in the following order: leaf > stalk+leaf > stalk. Among the CR from commercial crops, those of maize (leaf+stalk) were which presented least amount of C mineralized (39%). The mineralization of C from roots presents values similar to those observed for CR from shoot. The mineralization of N in the soil was significantly correlated with the total content of N in the DM and in the Van Soest soluble fraction of shoot and roots (P < 0.01 and r2 ranging from 0.90 to 0.98). The values of correlation between biochemical composition of CR and C mineralization were lower than those observed for N mineralization, but there was a greater number of significant correlations, especially for ratio C/N, polyphenols and NDF from Van Soest.